2013
DOI: 10.1093/hsw/hlt022
|View full text |Cite
|
Sign up to set email alerts
|

Better Colon Cancer Care for Extremely Poor Canadian Women Compared with American Women

Abstract: Extremely poor Canadian women were recently observed to be largely advantaged on most aspects of breast cancer care as compared with similarly poor, but much less adequately insured, women in the United States. This historical study systematically replicated the protective effects of single-versus multipayer health care by comparing colon cancer care among cohorts of extremely poor women in California and Ontario between 1996 and 2011. The Canadian women were again observed to have been largely advantaged. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
3
17
1
Order By: Relevance
“…Consistent with findings from previous research, 1420 having adequate health care insurance coverage predicted rates of OS while living in poverty and being a woman of color predicted rates of mortality. The women of color in our study were twice as likely to die within 7 years of being diagnosed with breast cancer than were non-Hispanic white women (HR = 2.28).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with findings from previous research, 1420 having adequate health care insurance coverage predicted rates of OS while living in poverty and being a woman of color predicted rates of mortality. The women of color in our study were twice as likely to die within 7 years of being diagnosed with breast cancer than were non-Hispanic white women (HR = 2.28).…”
Section: Resultssupporting
confidence: 88%
“…22–24 Based on previous analyses, primary health care insurance coverage was defined as adequate (private or Medicare) or inadequate (Medicaid or none). 15,16,1820 …”
Section: Methodsmentioning
confidence: 99%
“…89 Similar to curative treatment barriers observed among those with non-metastasised colon cancer and consistent with this field’s synthetic evidence, 41013 we and others have observed significant barriers to palliative chemotherapy among people living in poverty with metastasised colon cancer. 51415 Furthermore, our analyses found that prevalent health insurance inadequacies in America accounted for most, but not all of the poverty-based chemotherapy inadequacies, whether the intention was to cure or comfort. Our premise has been that focusing on the experiences of the most vulnerable people in the most vulnerable places magnifies clinical, policy and human significance.…”
Section: Introductionmentioning
confidence: 71%
“…Standardized rate ratios (RR) and rate differences (RD) were reported with 95% confidence intervals (CI). Further methodological details were published (Gorey et al, 2011(Gorey et al, , 2013. …”
mentioning
confidence: 99%
“…Colon cancer care, a common and treatable form of cancer, was studied among those living in poverty in 1990s and 2000s California (Gorey et al, 2011(Gorey et al, , 2013. Similar people were originally studied in Ontario.…”
mentioning
confidence: 99%